The murder man - Parsons, Tony, 1953- (Max Wolfe novels, 2014)
"Meet London police detective Max Wolfe. Insomniac. Dog lover. Coffee addict. Boxer. Single parent. And every murderer's worst nightmare. There's a serial killer on the loose. He cuts throats. And he is good at it. Twenty years ago seven students became best friends at their exclusive private school, Potter's Field, founded five hundred years ago by King Henry VIII. Suddenly they have started dying in the most violent way imaginable... Detective Max Wolfe follows the bloody trail from the backstreets and bright lights of London all the way to the corner rooms in the corridors of power. At enormous personal cost, what Wolfe uncovers is a horrific secret that has been buried for two decades--and is now coming back to haunt all of those involved. With this stunning crime fiction debut, award-winning journalist and international bestselling author Tony Parsons is poised for breakout success in the US"--